2021
DOI: 10.1177/11786329211054035
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Knowledge and Delayed Health Care Seeking Among New Diagnosed Tuberculosis Patients in Primary Health Facilities in an Urban District, South Africa

Abstract: Patients’ delay in seeking health care is a major problem in the control of tuberculosis (TB) and increases the risk of TB transmission. This study determined health-seeking practices and delays that occurred from the onset of TB symptoms until diagnosis and assessed the patients’ TB-related knowledge. This was a cross-sectional study involving 391 new TB patients recruited from health facilities at an urban sub-district in South Africa from December 2016 to March 2017. Descriptive statistics and logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
2
9
0
4
Order By: Relevance
“…It was lower than studies have done Tigray region showed that 44.8% [20][21][22][23][24], Gamo zone (56.9%) [25][26][27], South Africa (56.3%) [28], Nigeria (61.8%) [29], and North Wollo Zone (62.3%) of patients consult after control and prevention programs in low-and middleincome settings [13][14][15][16].…”
Section: Discussionmentioning
confidence: 90%
“…It was lower than studies have done Tigray region showed that 44.8% [20][21][22][23][24], Gamo zone (56.9%) [25][26][27], South Africa (56.3%) [28], Nigeria (61.8%) [29], and North Wollo Zone (62.3%) of patients consult after control and prevention programs in low-and middleincome settings [13][14][15][16].…”
Section: Discussionmentioning
confidence: 90%
“…Our feedback allowed the PHDC to update their data. While we acknowledge that patient-related factors also play a role in linkage [2,3,26,27], this study highlights key aspects within the TB program that can be targeted to improve linkage to TB care; improved data capturing, real-time data availability, improved communication between healthcare workers and persons with TB and updating contact details at every healthcare visit.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that people with TB symptoms delay seeking care for at least one month [12,13] which indicates that they contribute to sustained community transmission of TB. In this analysis the survey criteria for symptoms were a duration of at least two weeks for night sweats, weight loss, and fever, and although 60% of participants reported intention to seek care, our findings are nonetheless suggestive of delayed healthcare seeking consistent with…”
Section: Plos Onementioning
confidence: 99%
“…the literature [12,13]. Care seeking was delayed even among those who reported cough of 2 weeks or longer (S2 and S4 Tables).…”
Section: Plos Onementioning
confidence: 99%